2017
DOI: 10.1186/s13024-017-0198-4
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin reverts central pathology and cognitive impairment in diabetic mother offspring

Abstract: BackgroundAdverse effects in diabetic mothers offspring (DMO) are a major concern of increasing incidence. Among these, chronic central complications in DMO remain poorly understood, and in extreme cases, diabetes can essentially function as a gestational brain insult. Nevertheless, therapeutic alternatives for DMO are limited.MethodsTherefore, we have analyzed the central long-term complications in the offspring from CD1 diabetic mothers treated with streptozotozin, as well as the possible reversion of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The improvement of ER272 treated mice was similar to that found in healthy mice treated with insulin by intranasal administration [48]. This suggests that the effect of ER272 on memory tasks may be as potent as other neurogenic drugs such as insulin [48,49]. However, we have not been able to directly demonstrate that the induction of neurogenesis is responsible for the improvement in memory and learning tasks.…”
Section: Discussionmentioning
confidence: 54%
“…The improvement of ER272 treated mice was similar to that found in healthy mice treated with insulin by intranasal administration [48]. This suggests that the effect of ER272 on memory tasks may be as potent as other neurogenic drugs such as insulin [48,49]. However, we have not been able to directly demonstrate that the induction of neurogenesis is responsible for the improvement in memory and learning tasks.…”
Section: Discussionmentioning
confidence: 54%
“…Spine density was calculated (spines/10 μm) ( Infante-Garcia et al, 2015 ). Ratios of curvature were calculated by dividing the end-to-end distance of a dendrite segment by the total length between the two segment ends using Image J software ( Ramos-Rodriguez et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sections were dehydrated in 70% ethanol for 15 min. They were stained with cresyl violet (Sigma, St. Louis, MO, United States) solution (0.5% w/v) for 10 min, as previously described (Ramos-Rodriguez et al, 2017). Sections were then fixed sequentially in 0.25% acetic acid, 100% ethanol and xylene for 2 min.…”
Section: Cresyl Violet Stainingmentioning
confidence: 99%
“…Likewise, STZ-induced T1D rats present a significant reduction in hippocampus Ab levels when treated with intranasal insulin (180). Interestingly, it has been shown that long-term complications observed on brain of offspring from STZ-induced diabetic mothers could be completely reversed through the intranasal administration of insulin (153). Regarding AD, in vivo studies showed that intranasal insulin administration was able to restore proper brain insulin signaling, increase synaptic proteins, and reduce Ab level and microglia activation (45) and protected against neurodegeneration and recovered memory deficits (84).…”
Section: Insulin and Insulin Sensitizers: A Shortcut To Mitochondrialmentioning
confidence: 99%